Research on the Preparation of Irradiated-type 99Mo-99mTc Generator - Siwei GU; Ning LUO; Bo LI; Qinzhi LI; Yingjiang HU; Yunming CHEN; Jinsong ZHANG (Journal of Isotopes, 2024)
Due to the excellent nuclear properties，99mTc has been used in the field of early diagnosis of tumor and nuclear medicine imaging. As the most widely applied radioisotope，it accounts for more than 70% of the market of total radioisotopes used in the nuclear medicine diagnosis. Until now，99mTc in clinical has been prepared by the 99Mo-99mTc generators. To improve the disadvantages of current technologies including unstable supplement of the fission 99Mo for the fission-type 99Mo-99mTc generator and long production time for the gel-type 99Mo-99mTc generator，a new irradiated-type 99Mo-99mTc generator filled with the Ti99Mo has been developed. The effects of the chemical agents，Mo:Ti molar ratio，dry methods on the elution properties of the Ti99Mo-based 99Mo-99mTc generator were investigated. Based on the results of simulation experiments and performance tests，the elution from the irradiated-type 99Mo-99mTc generator was found to be accorded with medical standard. During the seven elution processes，the radionuclidic purity of sodium technetium-99m solution was above 99.92%，the radiochemical purity was higher than 98.8%，the pH value was between 5.0 and 6.0 and the average elution efficiency reached 72.07%，the peak of elute curve was located at 2-4 mL without the phenomenon of trailing，showing the excellent performance. The synthesized preparation has been advanced before the process of irradiation by the reactor，to simplify the operational radioactive procedures，shorten the production time，increase the elution efficiency of the generator and decrease the loss of 99Mo decay.